مشروعات تخرج طالبات قسم علم المعلومات بجامعة أم القرى : دراسة لاتجاهاتها الکمیة والمنهجیة والمشکلات التى تواجهها الطالبات - د. محمد محمد النجار (المجلة الدولية لعلوم المكتبات والمعلومات)
This paper aims to study the trends of graduation projects of female students at the information science department in Umm Al-Qura University. The study was conducted during the period of (1434-1435/1435-1436) with a total of70 projects. To achieve this, the researcher used content analysis the frequency statistics and trends of the graduation projects. This was done through designing content analysis cards which was divided into two parts. The first part includes personal information of the students such as: contact data, academic level, and their PA. The second part includes research methodology of projects such as: aims, approach, used sample type and data collecting tools.Results of the study includes the following:1. Constructive approach comes at the top rank with a percentage of (44.2%) from the total graduation projects.2. Random sample also comes at the top rank with a percentage of (65.7%) from the total graduation projects.3. The most used tool for data collection was the questionnaire which comes at the top with (72.8%) percent.In addition, this study aims at discover the problems facing the female students during their preparation of the graduation projects as per their point of view. The study included (80) students. To identify these problems, the researcher used survey methodology and prepared a questionnaire to be filled by the students. The questionnaire consisted of two parts: the first part included personal data of students in four sections; and the second part included (30) sections, out of which 14 are for administrative problems; 12 sections for research problems; and 4 sections for linguistic problems.In this regard, Results of the study includes the following:1. Within the administrative problems, the maximum number of credit hours registered for each student during the graduation project semester, came at the top of the problems and difficulties facing students with a mean of(2.64).2. Within the research problems, little experience using retrieval system came at the top of the problems and difficulties facing students with a mean of (1.78). Weakness in using correct language grammar for research comes at the top rank in the linguistic problems.The researcher suggests some recommendations aiming at improving graduation projects and their marketing.